Bilateral Simultaneous Full-Thickness Macular Holes: A Case Report with Spontaneous Resolution - Isabel López-Bernal; Ángel Sánchez Trancón; Pedro Serra (Reports)
Background and Clinical Significance: Full-thickness macular hole (FTMH) is a common retinal condition that impairs detailed vision, with idiopathic causes being the most prevalent. Small macular holes (<250 µm) have the potential for spontaneous closure, whereas larger holes typically require surgical intervention to restore visual acuity (VA). The management of small macular holes remains controversial, as approximately 25% resolve spontaneously. Reporting cases of spontaneous closure may provide evidence to support a conservative, non-surgical approach in such cases. Case Presentation: We report the case of a 65-year-old female patient monitored using spectral domain optical coherence tomography (OCT). She initially presented with unilateral FTMH and subsequently developed an FTMH in the fellow eye during follow-up. Both macular holes closed spontaneously, leading to VA recovery. OCT imaging enabled the identification of vitreomacular traction as the underlying mechanism for hole formation and the bridging process responsible for spontaneous closure. Conclusions: This case highlights the potential for spontaneous anatomical and functional recovery in small-diameter macular holes (<250 µm). A conservative, observational approach may be appropriate in selected cases, potentially avoiding unnecessary surgical intervention.